Developing English job interview skill using artificial intelligence technology - Dewanti Ratna Pertiwi; Maria Asumpta Deny Kusumaningrum (KACANEGARA Jurnal Pengabdian pada Masyarakat, 2021)
Vocational high schools (VHS) mainly prepare the students to engage in employment with a number of specific skills even though some students may continue to study in university/ college level. Various job vacancy advertisements require English skill in completing either the documents or interview. In competing the documents such as CV and cover letter, the students may adopt and adapt some templates even consult to the experts to get the best quality. However, in the interview, the students should perform themselves in live interaction. If the students are not well prepared, they may pass the documents selection but fail the interview step. Therefore, English job interview preparation is needed to equip the students ready in facing the job interview. Nowadays, artificial intelligence (AI) technology can help to improve the students’ speaking skill including job interview. The use of AI becomes higher due to the advantages such as flexibility, accurateness, and direct feedback. This program applied AI technology to develop English job interview skill in of the students in SMK AAG Penerbangan Adisutjipto Yogyakarta. The result was the selected AI successfully improved the students’ job interview skills indicated on the increased mark after applying the technology.